The surprisingly weak evidence base for supervision: Findings from a systematic review of research in child welfare practice (2000–2012) - Carpenter, John; Webb, Caroline M.; Bostock, Lisa (Children and youth services review, 2013)
The objective of this study is to ascertain what is known about the effectiveness and cost-effectiveness of supervision in child welfare in relation to outcomes for consumers/service users, staff and organizations. This is a systematic review of the English language literature (2000–2012). Scoping study is followed by database searches of indexes and abstracts including Campbell Collaboration, CINAHL, the Cochrane Library, Medline, PsycInfo and Social Work Abstracts, journal hosts (EBSCO and IngentaConnect) plus specialist journals. Inclusion criteria: studies that reported on the associations between the provision of supervision and outcomes for service users/consumers, workers and organizations as well as intervention studies. Potentially relevant studies were independently screened by two reviewers (Stage 1) and if meeting the eligibility criteria proceed to full text review and data extraction (Stage 2). Studies were subject to critical appraisal by three reviewers using the Weight of Evidence approach (Stage 3). An analysis of included study characteristics is followed by a narrative synthesis of findings structured to answer the research objective. 690 unique studies were identified at Stage 1, 35 proceeded to Stage 2 and, following quality appraisal, 21 were included in the review. Almost all of the studies were cross-sectional, providing evidence of associations between the provision of supervision and a variety of outcomes for workers, including job satisfaction, self-efficacy and stress and for organizations, including workload management, case analysis and retention. There was only one, poorly reported, intervention study and no studies of outcomes for consumers. No economic evaluations were found. The evidence base for the effectiveness of supervision in child welfare is surprisingly weak. An agenda for research based on a framework for the development and evaluation of complex interventions is proposed. •This systematic review found no high quality evidence for outcomes of supervision.•Study designs are weak and samples limited; supervision rarely defined.•Supervision is associated with worker satisfaction, self-efficacy and lower stress.•Outcomes for organizations may include workload management and retention.•No studies have investigated outcomes for consumers or the costs of supervision.